2008
DOI: 10.1016/j.dnarep.2008.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Mutator phenotype of mammalian cells due to deficiency of NEIL1 DNA glycosylase, an oxidized base-specific repair enzyme

Abstract: The recently characterized NEIL1 and NEIL2 are distinct from the previously characterized mammalian DNA glycosylases (OGG1 and NTH1) involved in repair of oxidized bases because of the NEILs' preference for excising base lesions from single-stranded DNA present in bubble and fork structures. OGG1 and NTH1 are active only with duplex DNA. This raises the possibility that NEILs function in the repair of base lesions during DNA replication and/or transcription. S-phasespecific activation of only NEIL1 suggests it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…We also identified a polymorphic variant of NEIL2 that occurs more frequently in human lung cancer patients than in normal individuals (19). Furthermore, depletion of NEIL2 caused a significant increase in the spontaneous mutation frequency in the HPRT gene of the V79 Chinese hamster lung cell line (20). All these studies collectively indicate that NEIL2 plays an important role in maintaining genomic integrity and preventing DNA mutagenesis in mammalian cells.…”
mentioning
confidence: 49%
“…We also identified a polymorphic variant of NEIL2 that occurs more frequently in human lung cancer patients than in normal individuals (19). Furthermore, depletion of NEIL2 caused a significant increase in the spontaneous mutation frequency in the HPRT gene of the V79 Chinese hamster lung cell line (20). All these studies collectively indicate that NEIL2 plays an important role in maintaining genomic integrity and preventing DNA mutagenesis in mammalian cells.…”
mentioning
confidence: 49%
“…The higher metal concentration required to cause a similar level of inhibition in cell versus in vitro may be due to metal absorption efficiency of the cells as well as their sequestering by cellular proteins. We showed earlier that NEIL1 down-regulation in mammalian cells results in elevated oxidative damage in the genome and increased spontaneous mutations (72). Further, NEILs play a vital role in repair of oxidized bases in brain cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, inactivating mutations of NEIL1 have been associated with gastric cancers [Shinmura et al, 2004]. Furthermore, cell culture studies have indicated that knock down of Neil1 renders cells more sensitive to oxidative stress, such as that induced by glucose oxidase or gamma irradiation [Rosenquist et al, 2003;Maiti et al, 2008]. NEIL1-deficient mice, although initially expected to display a promutagenic phenotype, have not been found to be significantly prone to spontaneous tumor formation, although lung adenomas and hepatocellular carcinomas have been documented in about 10-20% of aged animals [Chan et al, 2009].…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%